Evaluating the impact of a well-targeted wage subsidy using administrative data - Zsombor Cseres-Gergely; Ágota Scharle; Árpád Földessy (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
The paper measures the impact of a wage subsidy for long term unemployed workers, using a large administrative dataset from Hungary. While such subsidies are often promoted as an efficient way to speed up the recovery of the economy or to increase demand for low skilled workers, existing evidence on their employment effects is somewhat inconclusive, especially in the case of transition economies. We examine employment outcomes in various model specifications. Results show a significant impact for men aged over 50, which is driven by the subgroup of those with lower secondary education. The subsidy for jobseekers with at least secondary education and aged over 50 is cost effective for men. We also present some evidence that this is not merely caused by substitution across various sub-groups of jobseekers.
Keywords: J38; J68; 330; wage-subsidy; evaluation; older workers